Multifunctional P-Doped TiO2 films: a new approach to self-cleaning, transparent conducting oxide materials - Sotelo-Vazquez,C; Noor,N; Kafizas,A; Quesada-Cabrera,R; Scanlon,DO; Taylor,A; Durrant,JR; Parkin,IP (Chemistry of Materials, 2015)
Multifunctional P-doped TiO2 thin films were synthesized by atmospheric pressure chemical vapor deposition (APCVD). This is the first example of P-doped TiO2 films with both P5+ and P3– states, with the relative proportion being determined by synthesis conditions. This technique to control the oxidation state of the impurities presents a new approach to achieve films with both self-cleaning and TCO properties. The origin of electrical conductivity in these materials was correlated to the incorporation of P5+ species, as suggested by Hall Effect probe measurements. The photocatalytic performance of the films was investigated using the model organic pollutant, stearic acid, with films containing predominately P3– states found to be vastly inferior photocatalysts compared to undoped TiO2 films. Transient absorption spectroscopy studies also showed that charge carrier concentrations increased by several orders of magnitude in films containing P5+ species only, whereas photogenerated carrier lifetimes—and thus photocatalytic activity—were severely reduced upon incorporation of P3– species. The results presented here provide important insights on the influence of dopant nature and location within a semiconductor structure. These new P-doped TiO2 films are a breakthrough in the development of multifunctional advanced materials with tuned properties for a wide range of applications.